IMPLEMENTASI ALGORITMA ITERATIVE DICHOTOMIZER 3 UNTUK DIAGNOSIS PENYAKIT GASTROENTERITIS ANAK BERBASIS WEB - M. Karman Habibi; Veri Julianto; M. Najamudin Ridha; Fathurrahmani, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Gastroenteritis is a disease that affects the digestive system, causing symptoms such as nausea, vomiting, diarrhea, abdominal cramps, and dehydration. Lack of knowledge and delayed diagnosis often worsen the condition of children affected by gastroenteritis. Therefore, early awareness is needed to prevent wider spread. The ID3 algorithm, which performs an exhaustive search of all possible decision trees, is used in this study to predict gastroenteritis in children. Data from 69 affected children and 61 unaffected children at RSUD Hadji Boejasin Pelaihari shows that the ID3 algorithm achieved an accuracy of 86.6%, precision of 92.3%, and sensitivity of 80%. The implementation of this algorithm in a web-based application is expected to provide useful information for the early diagnosis of gastroenteritis.